SLEEP DISORDERED BREATHING IN RENAL TRANSPLANT PATIENTS: A LONGITUDINAL STUDY. (June 2018) - Mallamaci, F.; Tripepi, R.; D'Arrigo, G.; Porto, G.; Marino, C.; Sanguedolce, M.C.; Tripepi, G.; Zoccali, C.
Abstract : Objective: Sleep disordered breathing (SDB) is a pervasive problem in stage 5 CKD patients maintained on regular dialysis treatment. Renal transplantation improves SDB but the longitudinal, long term evolution of SDB after kidney grafting has not been investigated. The issue is relevant because renal transplantation abolishes uremic toxicity but introduces classical risk factors for SDB, like overweight and obesity. Design and method: We investigated the long term evolution of polysomnographic recordings in 221 stable renal transplant patients. Overall 404 recordings over a median time of 3 years (interquartile range 2 – 4) were performed. Longitudinal analysis was performed by the linear mixed model (LMM). Results: The apnea-hypopnea index (AHI) in renal transplant patients was 5.44 ± SD 0.75 and the corresponding number of O2 desaturation (Des O2) episodes was 4.40 ± 0.60. The number of patients with AHI > 5 (the threshold for identifying mild SDB) rose from 25% at baseline to 43% at the end of the follow up. Over follow-up the AHI rose to 9.94 ± 2.37 (P < 0.001) and the number of desaturation episodes to 5.55 ± 2.1 (P = 0.010) which went along with a decline in the mean O2-saturation overnight (Mean SatO2: from 95.08 ± 0.14 to 94.64 ± 0.32, P = 0.001). LMM showed that age, sex, BMI, ESA treatment but neither eGFR nor the presence of proteinuria associated with the AHI. On multivariate analyses only male gender (3.42; 95%CI: 0.35 to 6.49; P = 0.003) and BMI (0.87; 95% CI 0.46 to 1.27; P < 0.001) associated with the AHI evolution over follow-up. Similar associations were registered also for the other parameters of SDB (Des O2, Mean Sat O2). Conclusions: Even though renal transplantation produces an early improvement in SDB in renal transplant patients, this treatment does not stabilize the disturbance which gradually re-emerges over longitudinal observation. Among risk factors underlying the risk of SDB re-emergence after transplantation the rise in BMI, i.e. a modifiable risk factor, appears to be of paramount importance. Tackling the surge of SDB after transplantation is of obvious relevance because this disturbance is a potent driver of sympathetic over-activity and of the attendant risk of cardiovascular events in this population.